2002
DOI: 10.1109/jproc.2002.1002525
|View full text |Cite
|
Sign up to set email alerts
|

Color plasma displays

Abstract: After decades of research and development, plasma displays are finally beginning to appear in the commercial and consumer markets. Following a short review on the basic principles of direct and alternating current plasma displays, we present a summary of the status of color plasma displays. Plasma display panels (PDPs) have finally achieved luminance and efficiency values on par with hi-definition cathode ray tube monitors. Additional improvements in performance will open up a new world of large PDP displays. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 8 publications
(8 reference statements)
0
16
0
Order By: Relevance
“…The solvent was removed to afford the product as dark red crystals that were recrystallized from chloroform to afford 1.30 g, (59 %). 1 Poly(2,7-(9-(2¢-ethylhexyl)-9-hexyl-fluorene)-alt-5,5-(4¢,7¢-di-2-thienyl-2¢,1¢,3¢-benzothiadiazole)) (PFDTBT): 4,7-Di-2¢-(5¢-bromo)-thienyl-2,1,3-benzothiadiazole (0.15 g, 0.33 mmol) was mixed with 2,7-bis(4¢,4¢,5¢,5¢-tetramethyl-1¢,3¢,2¢-dioxaborolan-2¢-yl)-9-(2¢¢-ethylhexyl)-9-hexylfluorene (0.22 g, 0.36 mmol, 1.1 equiv), tetrakis(triphenylphosphine)Pd(0) (3.0 mg, 2.6 lmol) and toluene (6 mL) and refluxed for 10 min under N 2 . Tetraethylammonium hydroxide (1.0 mL, 20 wt.-% in water, 1.4 mmol) was added with a syringe and the mixture was refluxed for 2.5 h. Bromobenzene (0.05 g, 0.32 mmol) was added and after 1 h reflux phenylboronic acid (0.06 g, 0.5 mmol) was added.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The solvent was removed to afford the product as dark red crystals that were recrystallized from chloroform to afford 1.30 g, (59 %). 1 Poly(2,7-(9-(2¢-ethylhexyl)-9-hexyl-fluorene)-alt-5,5-(4¢,7¢-di-2-thienyl-2¢,1¢,3¢-benzothiadiazole)) (PFDTBT): 4,7-Di-2¢-(5¢-bromo)-thienyl-2,1,3-benzothiadiazole (0.15 g, 0.33 mmol) was mixed with 2,7-bis(4¢,4¢,5¢,5¢-tetramethyl-1¢,3¢,2¢-dioxaborolan-2¢-yl)-9-(2¢¢-ethylhexyl)-9-hexylfluorene (0.22 g, 0.36 mmol, 1.1 equiv), tetrakis(triphenylphosphine)Pd(0) (3.0 mg, 2.6 lmol) and toluene (6 mL) and refluxed for 10 min under N 2 . Tetraethylammonium hydroxide (1.0 mL, 20 wt.-% in water, 1.4 mmol) was added with a syringe and the mixture was refluxed for 2.5 h. Bromobenzene (0.05 g, 0.32 mmol) was added and after 1 h reflux phenylboronic acid (0.06 g, 0.5 mmol) was added.…”
Section: Methodsmentioning
confidence: 99%
“…[14] ± Formation of Polarization Gratings and Surface Relief Gratings in Photocrosslinkable Polymer Liquid Crystals by Polarization Holography** By Nobuhiro Kawatsuki,* Takako Hasegawa, Hiroshi Ono,* and Takashi Tamoto As a result of the myriad of potential applications such as optical memory devices, thin film optical filters, and integrated optical devices, photoinduced orientation in photosensitive polymer systems has received a great deal of attention. [1,2] One area well researched is holographic diffractive elements, and several types of photosensitive materials have been developed into new holographic grating devices, including photochromic polymers [3±6] and photoreactive polymers. [7,8] Numerous studies reported that irradiating polymers containing azobenzene side groups with linearly polarized…”
Section: Methodsmentioning
confidence: 99%
“…For example, it is used in neon glow lamps, in indicators glow tube [13], in starters [14], in sodium-vapor lamp, and in gas arresters [15]. Beside of that, recently neon has applications in plasma panels, in mixture with a small percentage of Xe or Ar [16].…”
Section: Introductionmentioning
confidence: 99%
“…Also, as light-emissive devices, PDPs have the advantages of wide viewing angle and vivid color. Many researches are being carried out to further improve the performance of PDPs [1].…”
Section: Introductionmentioning
confidence: 99%